Incidence and Significance of Intraoperative CSF Leak in Endoscopic Pituitary Surgery Using Intrathecal Fluorescein - Jakimovski, D.; Bonci, G.; Attia, M.; Shao, H.; Hofstetter, C.; Tsiouris, A. J.; Anand, V. K.; Schwartz, T. H. (Journal of neurological surgery. Part B, Skull base, 2012)
Objective: The true rate of intraoperative (i)CSF leak during pituitary surgery is not well known because small iCSF leaks are easily missed. Our objective is to determine the rate and significance of iCSF leak in endoscopic pituitary surgery with intrathecal fluorescein administration. Design: Retrospective study. Materials and Methods: Intrathecal fluorescein was administered in 203 consecutive endoscopic endonasal pituitary surgeries. The rate of iCSF leak was correlated with tumor diameter and volume, rate of gross total resection (GTR), and the learning curve. Postoperative CSF leak rate, complications, and nasoseptal (NS) flap utility were also investigated. Results: The rate of iCSF leak was 61% overall; it was 44% for tumors <2 cm compared with 72% for tumors ≥2 cm; it was 35% for tumors <1.5 cm compared with 68% for those ≥1.5 cm ( P < 0.001). GTR and the learning curve did not influence iCSF leak rates. Re-operations had a higher rate of iCSF leak only for tumors >2 cm. Postoperative CSF leak was significantly lower after the learning curve was completed (0.7% versus 10%; P < 0.005). For tumors >2 cm, the introduction of NS flap reduced the rate of postoperative CSF leak from 5.6% to 1.4%. We did not find any complications clearly related with the use of intrathecal fluorescein. Conclusions: Tumor diameter and volume are the best predictors of the risk of iCSF leak. Based on this knowledge and a closure algorithm that includes NS flap for larger tumors (>2.5 cm), the postoperative CSF leak rate remains exceptionally low, particularly once the learning curve is overcome.